Resiliensi dan Stres Akademik Mahasiswa Yang Sedang Menyelesaikan Skripsi di Universitas X Jakarta Barat - Aulia Kirana; Agustini Agustini; Enka Rista (Provitae: Jurnal Psikologi Pendidikan, 2022)
This study aims to examine the relationship between Resilience and academic stress of students who are completing their final project at X University, West Jakarta. The sample in the study amounted to 87 respondents consisting of 33 men and 54 women. The sampling technique used was non-probability sampling with the convenience sampling method. The measuring instrument in this study used the instrument of academic stress and resilience. The results obtained are correlation coefficient (r) -0.324 and a significance value of 0.002 (p <0.01). It can be concluded that there is a negative relationship between academic stress and resilience in students who are completing their final project at University X, West Jakarta. This shows that the higher the academic stress, the lower the resilience of students who are completing their final assignments and vice versa if the lower the academic stress of students who are completing their final assignments at University X, West Jakarta.